The Remarkable Metabolism of Vickermania ingenoplastis: Genomic Predictions - Opperdoes, Fred R; Butenko, Anzhelika; Zakharova, Alexandra; Gerasimov, Evgeny S; Zimmer, Sara L; Lukeš, Julius; Yurchenko, Vyacheslav (Pathogens (Basel, Switzerland), 2021)
A recently redescribed two-flagellar trypanosomatid Vickermania ingenoplastis is insensitive to the classical inhibitors of respiration and thrives under anaerobic conditions. Using genomic and transcriptomic data, we analyzed its genes of the core metabolism and documented that subunits of the mitochondrial respiratory complexes III and IV are ablated, while those of complexes I, II, and V are all present, along with an alternative oxidase. This explains the previously reported conversion of glucose to acetate and succinate by aerobic fermentation. Glycolytic pyruvate is metabolized to acetate and ethanol by pyruvate dismutation, whereby a unique type of alcohol dehydrogenase (shared only with Phytomonas spp.) processes an excess of reducing equivalents formed under anaerobic conditions, leading to the formation of ethanol. Succinate (formed to maintain the glycosomal redox balance) is converted to propionate by a cyclic process involving three enzymes of the mitochondrial methyl-malonyl-CoA pathway, via a cyclic process, which results in the formation of additional ATP. The unusual structure of the V. ingenoplastis genome and its similarity with that of Phytomonas spp. imply their relatedness or convergent evolution. Nevertheless, a critical difference between these two trypanosomatids is that the former has significantly increased its genome size by gene duplications, while the latter streamlined its genome.
Keywords: Vickermania ingenoplastis; genome sequencing; metabolism; Phytomonas